Burden of Intracranial Atherosclerosis Is Associated With Long-Term Vascular Outcome in Patients With Ischemic Stroke. Issue 10 (October 2017) - Kim, Byung-Su; Chung, Pil-Wook; Park, Kwang-Yeol; Won, Hong-Hee; Bang, Oh Young; Chung, Chin-Sang; Lee, Kwang Ho; Kim, Gyeong-Moon
Abstract : Background and Purpose—: Ischemic stroke patients often have intracranial atherosclerosis (ICAS), despite heterogeneity in the cause of stroke. We tested the hypothesis that ICAS burden can independently reflect the risk of long-term vascular outcome. Methods—: This was a retrospective cohort study analyzing data from a prospective stroke registry enrolling consecutive patients with acute ischemic stroke or transient ischemic attack. A total of 1081 patients were categorized into no ICAS, single ICAS, and advanced ICAS (ICAS ≥2 different intracranial arteries) groups. Primary and secondary end points were time to occurrence of recurrent ischemic stroke and composite vascular outcome, respectively. Study end points by ICAS burden were compared using Cox proportional hazards models in overall and propensity-matched patients. Results—: ICAS was present in 405 patients (37.3%). During a median 5-year follow-up, recurrent stroke and composite vascular outcome occurred in 6.8% and 16.8% of patients, respectively. As the number of ICAS increased, the risk for study end points increased after adjustment of potential covariates (hazard ratio per 1 increase in ICAS, 1.19; 95% confidence interval, 1.01–1.42 for recurrent ischemic stroke and hazard ratio, 1.18; 95% confidence interval, 1.05–1.33 for composite vascular outcome). The hazard ratios (95% confidence interval) for recurrent stroke and composite vascular outcome in patients with advanced ICAS compared with those without ICAS were 1.56 (0.88–2.74) and 1.72 (1.17–2.53), respectively, in the overall patients. The corresponding values in the propensity-matched patients were 1.28 (0.71–2.30) and 1.95 (1.27–2.99), respectively. Conclusions—: ICAS burden was independently associated with the risk of subsequent composite vascular outcome in patients with ischemic stroke. These findings suggest that ICAS burden can reflect the risk of long-term vascular outcome. Abstract : Supplemental Digital Content is available in the text.